The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1111/jfbc.12352
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and antioxidant activities of polysaccharides extracted from enzymatic hydrolysate of Ginkgo biloba leaves

Abstract: Three high purified polysaccharide monomers (GBP11, GBP22, and GBP33) were obtained from enzymatic hydrolysate of Ginkgo biloba leave using DEAE‐Sepharose Fast Flow column and Sephadex G‐100 column, and their basic structural characterization were investigated by utilizing high‐performance liquid chromatography, high‐performance ion chromatography, and Infrared Spectroscopy. In addition, antioxidant activities of related polysaccharides were also evaluated. The results showed that the molecular weight of GBP11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Furthermore, oxidative stress is recognized as a significant contributing factor to various chronic diseases, including cancer. Polysaccharides from Ginkgo biloba leaves (GBPS) exhibit remarkable activities in scavenging hydroxyl and ABTS free radicals, enhancing antioxidant enzyme activities, and preventing oxidative damage to cellular DNA and other molecules, thus providing an effective defense mechanism ( 131 , 132 ). Additionally, the antibacterial properties of polysaccharides also show potential in cancer treatment.…”
Section: Effect Of Polysaccharides On Colon Cancer Progressionmentioning
confidence: 99%
“…Furthermore, oxidative stress is recognized as a significant contributing factor to various chronic diseases, including cancer. Polysaccharides from Ginkgo biloba leaves (GBPS) exhibit remarkable activities in scavenging hydroxyl and ABTS free radicals, enhancing antioxidant enzyme activities, and preventing oxidative damage to cellular DNA and other molecules, thus providing an effective defense mechanism ( 131 , 132 ). Additionally, the antibacterial properties of polysaccharides also show potential in cancer treatment.…”
Section: Effect Of Polysaccharides On Colon Cancer Progressionmentioning
confidence: 99%
“…All studies have shown a positive damping effect on the developing inflammation. The most commonly observed reductions in nitric oxide, interferon, prostaglandin E2, TNF-α, IL-1, IL-4, IL-6, IL-12, and IL-1β were observed in inflamed tissues [ 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ], as well as inter alia, changes in MAPK and NF-κB signaling pathways [ 116 , 122 ], caused, inter alia, by weaker translocation of the nuclear factor NF-κB [ 131 , 132 ]. In addition, there is also increased activation of AMPK protein kinase [ 122 ] and heme oxygenase [ 130 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…These analyzes were carried out using various methods (e.g., DPPH, ABTS, scavenging hydroxyl radicals or superoxide anion methods), which does not allow for a direct comparison of the results of all these studies. However, all studies showed the antioxidant activity of the tested substrates, often assessed as high or very high [ 21 , 126 , 131 , 138 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ]. However, it was noted that this activity varies depending on the date of leaf harvest: it is the highest in the case of raw material harvested in autumn [ 68 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…DPPH free radicals scavenging activity DPPH free radicals scavenging activity of BHCP was evaluated using the method reported (Hu et al, 2021;Zhang et al, 2017) with some modifications. First, a series of BHCP solutions (50, 100, 200, 500, 1000, 2000 μg/mL) were prepared, respectively.…”
Section: Antioxidant Activities In Vitromentioning
confidence: 99%